A Public Theological Response to Gender-based and Sexual Violence in Indonesia - Erich von Marthin Elraphoma (Theologia in Loco, 2022)
Gender-based and sexual violence is a public concern. In Indonesian society, three prominent entities (the state, the academy, and the religion) must provide their perspectives to overcome and prevent all forms of gender-based and sexual violence. On the one hand, the state exists via policies in the form of laws related to the prevention and solution to the problems of gender-based violence and sexual violence. As organizations and organisms, on the other hand, academia and religions contribute to the beliefs, concepts, and practices of gender and human sexuality. As a religious institution, the church’s action to prevent gender-based and sexual violence is also a form of self-criticism. The church may sanctify violence through gender-biased Bible reading or even commit gender-based violence and or sexual violence against its congregation members through its pastors. The church’s understanding of gender and sexual-based violence will allow the church to collaborate with the state to provide a sense of justice, security, and peace for all people, transcending the limitations of gender differences and sexuality. The church can offer theological concepts and practices that address and prevent gender-sexual-based violence both in church and in society in two ways: By reflecting on the experiences of victims of gender-based and sexual violence and by re-examining the root factors of violence in the history of the church and the church’s teaching on gender and sexuality, I propose that the church emphasize the diversity of God’s creation and the equal relations among humans beyond sexual and gender particularity by redefining the human body in Christian Theology that will serve as the foundation for resisting sexual violence and discrimination.